Sperm quality of Colossoma macropomum after room-temperature and cold storage - Pires, Luana Barbosa; Sanches, Eduardo Antonio [UNESP]; Romagosa, Elizabeth; Corrêa Filho, Ruy Alberto Caetano; Nass, Rosiane Araujo Rodrigues; Lopera-Barrero, Nelson Mauricio; Povh, Jayme Aparecido (Hindawi, 2019)
The objective of this study was to evaluate the effects of cold and room-temperature storage on the quality of Colossoma macropomum sperm. The experiment was carried out in December (end of Spring), in Nova Mutum-MT, Brazil, involving nine C. macropomum males (4 years old; 6.4 ± 1.5 kg average weight). The fish were selected and transferred to masonry tanks (4 m3) in a laboratory (water renewal rate: 10 L/s; average water temperature: 28°C). Subsequently, reproduction was induced using 2.5 mg of crude carp pituitary extract/kg and the semen was harvested 240 degree hours after hormonal induction. The following sperm characteristics were analyzed every 5 hr using ImageJ/casa software: total motility (MOT), curvilinear velocity (VCL), average path velocity (VAP), straight-line velocity (VSL), straightness of sperm path (STR), wobble (WOB), progressive motility (PROG), beat cross frequency (BCF) and total number of spermatozoa (NSPZ). A fresh sample of semen from each animal was kept at room temperature (25.3 ± 1.2°C). For analysis of cooled semen, syringes were kept in cooling boxes at an average temperature of 16.9 ± 2.1°C. The reduction (p < 0.05) of MOT in semen kept at room temperature occurred at 10 hr (13.95%); in cooled semen, however, MOT declined at 15 hr (76.87%). At 15 hr, there was practically no MOT in the semen kept at room temperature (0.20%), whereas in the cooled semen this situation was observed only at 35 hr (2.91%) The MOT of cooled sperm was higher (p < 0.05) at all times (except zero time), compared with the semen maintained at room temperature. At 15 hr, the cooled spermatozoa showed higher (p < 0.05) VCL (142.18 μm/s) and BCF (29.72 Hz) than those maintained at room temperature (VCL: 51.18 μm/s; BCF: 19.57 Hz). After 15 hr, only the cooled sperm showed quality. In conclusion, semen cooling allows for extending the viability of C. macropomum spermatozoa from 5 to 10 hr without compromising their quality in most characteristics. At 15 and 25 hr of cooling, sperm viability is still observed, though with decreased quality.